2006
DOI: 10.1002/jcb.20922
|View full text |Cite
|
Sign up to set email alerts
|

FAP‐1‐mediated activation of NF‐κB induces resistance of head and neck cancer to fas‐induced apoptosis

Abstract: Molecular mechanisms responsible for tumor resistance to apoptosis often involve the Fas/FasL pathway. While squamous cell carcinomas of the head and neck (SCCHN) express both Fas and FasL, their resistance to self-induced apoptosis or apoptosis mediated by Fas agonistic antibody (CH-11Ab) was independent of the level of Fas surface expression or the presence of soluble Fas in supernatants of primary or metastatic SCCHN cell lines. By in vitro immunoselection, using PCI-15A cell line treated with successive cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 39 publications
0
24
0
Order By: Relevance
“…All these genetic events lead to increased NF-κB transcriptional activity, thus indicating that NF-κB target genes might control important steps for cellular transformation or cancer progression. It was reported that NF-κB may control not only apoptosis and cell cycle progression, but also invasion and metastasis [22,23]. 3.…”
Section: Parthenolide Inhibits Nf-κb Activationmentioning
confidence: 99%
“…All these genetic events lead to increased NF-κB transcriptional activity, thus indicating that NF-κB target genes might control important steps for cellular transformation or cancer progression. It was reported that NF-κB may control not only apoptosis and cell cycle progression, but also invasion and metastasis [22,23]. 3.…”
Section: Parthenolide Inhibits Nf-κb Activationmentioning
confidence: 99%
“…PTPL1 expression was reported to inhibit Fas-mediated apoptosis in both pancreatic adenocarcinoma [45,46] and melanoma [47] cell lines thus acting as a survival mechanism in tumor cells expressing both Fas and FasL. Additional tumor models of ovarian cancer [48], colon cancer [49], head/ neck cancer [50], hepatocellular carcinoma [51], and hepatoblastoma [52] also showed a correlation between tumor cell survival in the presence of both Fas/FasL and expression of PTPL1. While some functional and correlative evidence exists for the regulation of Fas by PTPL1, at least one potential mechanism is explored below.…”
Section: Ptpl1 As a Tumor Promotermentioning
confidence: 99%
“…FAP-1 overexpression has been reported to inhibit Fas-mediated apoptosis in certain human malignant cells, by acting as a negative switch in the Fas/FasL pathway, thereby providing them with a marked survival advantage (32,33). Moreover, silencing of FAP-1 gene expression or inhibition of FAP-1 protein tyrosine phosphatase (PTP) activity could abolish tumor cell resistance to Fas-induced apoptosis in a head and neck cancer model system (SCCHN cells) (105). In contrast, FADD protein, another critical component that positively regulates the Fas/FasL apoptotic potency (intermediates between the activated Fas and immature Caspase-8) (12,26,33), might not essentially contribute to cisplatin-induced apoptosis of RT4 and T24 cells, since the corresponding FADD gene activities in response to the drug remained unaffected in both cell types examined (data not shown).…”
Section: Discussionmentioning
confidence: 99%